Befriending Religious Others: From Religious Moderation to Religious Mediation in Indonesia - Adiprasetya, Joas (The ecumenical review, 2024)
This article offers a critique of the Indonesian government–led religious moderation programme, highlighting its limitations as a top-down political initiative primarily focused on national stability and security. Drawing on philosophical and theological perspectives, the article proposes an alternative: a friendship-based model of religious mediation. This approach emphasizes grassroots, everyday interfaith interactions to foster mutual understanding, respect for diversity, and genuine relational engagement. The friendship model is contrasted with tolerance-based frameworks inherent in the religious moderation programme, arguing for a shift from mere coexistence to the cultivation of meaningful, transformative interfaith relationships. By incorporating the “middle way” approach, this study suggests that nurturing healthy interfaith relations requires a synergy between grassroots initiatives, non-governmental educational efforts, and governmental support, offering a robust pathway to living together in the pluralistic Indonesian society.